Determination of Improved Efficacy and Stability of Silymarin Loaded Nanocochleates Over Liposomes for the Treatment of Skin Diseases - Rukhsana Rub; Neha Munot; Akshay Wadate (Current Aspects in Pharmaceutical Research and Development Vol. 6, 2021)
Aim: Silymarin, a complex polyphenolic component mixture with anti-oxidant, anti-inflammatory, and membrane-stabilizing property is being investigated in several dermatological conditions. Present research aims to evaluate potential of silymarin loaded nanocochleates and liposomal topical application for treating chronic skin diseases. Objectives: present study was carried out with the objectives to prepare and evaluate Silymarin loaded liposomes and optimize the same. Conversion of these liposomes into nanocochleates for improved efficacy in terms of drug entrapment, antimicrobial activity, cytotoxicity to HaCaT cell lines and short term stability studies. Study Design: Silymarin loaded liposomes and nanocochleates were formulated and optimized using Design Expert software. Different invitro and exvivo tests were performed to compare their performance. Methodology: Liposomes were prepared using ethanol injection method and further treated with calcium chloride to form nanocochleates by trapping method. Design of experiments (32 Factorial Design) was used for optimization of nanocochleates. Cell line studies (HaCaT cell lines) and short term stability studies were performed to compare the efficacy and stability respectively. Results: Particle size, entrapment efficiency and drug deposition in Wistar Rat Skin was found to be statistically significant for nanocochleates over liposomes proving superiority of cochleates. Both the carriers sustained release of silymarin for 24h. Antimicrobial efficacy of nanocochleates against E.coli and S.aureus was significant. Inhibition of hyper proliferation of HaCaT cell lines (key mechanism by which most of the antipsoriatic drugs act) demonstrated the superiority of nanocochleates over liposomes. Nanocochleates also displayed better stability compared to liposomes due to decreased entrapment efficacy and leakage of drug. Conclusion: Silymarin loaded Nanocochleates could prove as a promising topical drug delivery system for the treatment of chronic skin diseases like psoriasis.